(untitled) - Bacal, Robert (New York, 2005)
A satisfied customer is a loyal customer, and in today's supercompetitive business economy few things are as crucial to a company's bottom line as the quality of its customer service. This latest title in the popular Perfect Phrases series is just the thing for customer service employees and those who train and manage them. Perfect Phrases for Customer Service gets you quickly up and running with everything you need to keep customers happy and loyal, including: Clear explanations of the reasons for difficult customer behaviors. Proven tools and techniques for successfully handling even the most cantankerous customers. 101 dialogues and scripts organized according to types of difficult behaviors, usable as is or as part of a training program, and easily tailored to any industry and company culture
Keywords: Customer services,Customer services; Dịch vụ khách hàng,Dịch vụ khách hàng